AKTIVITAS FOTOKATALITIK BEADS TiO2-N/ZEOLIT-KITOSAN PADA FOTODEGRADASI METILEN BIRU (KAJIAN PENGEMBANAN, SUMBER SINAR DAN LAMA PENYINARAN) - Sri Wardhani; Akhmad Bahari; Muhammad Misbah Khunur (Journal of Environmental Engineering and Sustainable Technology, 2016)
Photodegradation is the decomposition of the compound semiconductor with light. This study aims to determine the photocatalytic activity of TiO2-N / zeolite-chitosan granules by studying the effect of TiO2-N impregnation on zeolites, light source, and the effect of exposure time on the photodegradation of Methylene Blue (MB). Zeolites are activated with HCl 0.4 M. TiO2-N synthesized by the method of sonication with urea as N source, then TiO2-N impregnated into the zeolite. Beads photocatalyst TiO2-N/zeolite-chitosan synthesized by mixing chitosan / acetic acid with a photocatalyst then dripped by syringe pump into 0.4 M NaOH to form granules. The energy band gap of the photocatalyst was determined by Reflactance Diffuse Spectroscopy (DRS). Beads photocatalyst TiO2-N/zeolite-chitosan tested their activity by adding 0,1g beads photocatalyst TiO2-N/zeolite-chitosan with 25 mL MB 20 mg / L and irradiated with sunlight/UV for 1-5 hours. The characterization results DRS beads photocatalyst TiO2-N/zeolite-chitosan has an energy band gap of 2.4 eV. The results showed that impregnation on zeolites can increase photodegradation MB. Light source also affects the catalytic activity of TiO2-N / zeolite-chitosan beads, sunlight provides greater activity than UV rays. The longer the exposure to the sun for up to 5 hours, TiO2-N/zeolite-chitosan granules can degrade MB amounted to 55.08%.Keywords: beads, TiO2-N, Methylene Blue, zeolite, chitosan.